(untitled) (Research, Society and Development, 2020)
Granular cell tumor (GCT) is an uncommon benign neoplasm of neural origin that affects soft tissues. It has a predilection for females between the 4th and 6th decades of life and its clinically presented as a painless submucosal nodule on tongue. The treatment of choice is the total removal of the lesion, presenting a good prognosis, with rare cases of recurrence. The aim of this study was to report a case of granular cell tumor in a female patient, located on tongue, with about 3 years of evolution. The lesion was completely removed, and the patient remains without signs of recurrence. Thus, the granular cell tumor must be considered as a differential diagnosis of submucosal nodular lesions on tongue.